Can Big Data Benefits Bridge Between Data Driven Supply Chain Orientation and Financial Performance? Evidence from Manufacturing Sector of Thailand - Komson Sommanawat; Tanapon Vipaporn; Watcharin Joemsittiprasert (International Journal of Supply Chain Management, 2019)
With the digitalization of industry, many of business operations depend upon the data which either support them or reject them due to versatile reasons. Such data has been managing through big data analytics now which has diverse benefits ranged from transaction to strategic benefits. However, their implication on financial performance of manufacturing firms in Thailand has stayed as grey area in literature. This study has aimed to analyze the impact of data driven supply chain orientation on financial performance in manufacturing firms of Thailand in mediating role of transactional, transformational, strategic and informational benefits of big data. Almost 42 manufacturing organizations have been surveyed in this regard which were currently engaged in big data operations and data has been collected from their employees through questionnaire. SEM and CFA were run to analyze the data to analyze hypotheses and model fitness respectively. Results have depicted that data driven supply chain significantly enhances financial performance through big data benefits and also in its direct path too. This study can help manufacturing firms in Asia to incorporate big data analytics in their manufacturing systems to ensure good financial health.